From Classroom to Hospitality Industry: Pelatihan Bahasa Inggris Pariwisata bagi Siswa SMKN Kesehatan dan Pariwisata Bangkinang - Dzulhijjah Yetti; Rahmad Akbar; Hayatul Khairul Rahmat; Nurkholis Nurkholis; Antoni Pribadi (PT Hakhara Akademia Indonesia, 2025)
This community service program aimed to enhance the English communication skills of students at SMKN Kesehatan dan Pariwisata Bangkinang through an English for Tourism training program based on a practice-based learning approach. The program was initiated in response to students’ limited practical communication abilities in hospitality contexts, resulting from the predominance of general English instruction that often lacks direct relevance to industry needs. The training employed a participatory approach consisting of needs assessment, contextual material development, interactive learning activities through role-play and service simulations, and comprehensive evaluation using pre-tests, post-tests, performance assessments, and observations. The participants were 56 eleventh-grade students from the Hospitality Study Program. The results demonstrated a significant improvement in students’ English communication competence, as indicated by an increase in the average score from 58 in the pre-test to 78 in the post-test. Improvements were observed across various aspects of communication, including pronunciation, vocabulary, fluency, grammar, and appropriateness of language use. Furthermore, students showed greater confidence, participation, and readiness to communicate in practical hospitality situations such as front office services, restaurant services, and tour guiding activities. The findings suggest that integrating English for Specific Purposes (ESP), particularly English for Tourism, with practice-based learning is effective in improving students’ communication skills and workplace readiness. Therefore, this training model can serve as a relevant and applicable strategy for strengthening vocational education, particularly in the tourism and hospitality sectors.